Narratives of Human Trafficking: Ways of Seeing and Not Seeing the Real Survivors and Stories - De Angelis, Maria (Narrative Works)

(untitled) (The University of New Brunswick, 2017)
The 2016 McKendy Lecture addressed the two grand narratives in the migration-crime-security nexus and critique their impact on our ability to see and not see real survivors and their stories of being trafficked. Focussing on the UK and female survivors, the lecture explored the crime master narrative for its construction of the social and cultural template—the official way of seeing the “right sort” of crime victim in trafficking (the VoT or modern slave). From this standpoint, anyone falling short of the template is susceptible to criminal scrutiny as someone culpable in her own exploitation. Similarly, the lecture examined the security narrative for its construction of the social and cultural template—the official way of seeing the “wrong sort” of migrant (undocumented, unskilled and racially different). Borne of political, social and cultural attitudes to UK immigration, the security narrative hides the reality of a migrant labour force without rights of citizenship or belonging. The lecture also shared stories of survivors of trafficking which illustrate how they are seen or not seen, but which survivors tell to promote their political visibility.